2022
DOI: 10.21037/tcr-21-2325
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of autophagy and PI3K/mTOR pathway as a potential therapeutic strategy against laryngeal squamous cell carcinoma

Abstract: Background New and effective chemotherapy or targeted therapy strategies are needed against laryngeal squamous cell carcinoma (LSCC). We aimed to explore the antitumor effect of dual PI3K/mTOR inhibitor combined with autophagy suppression on LSCC and its underlying mechanism. Methods Hep-2 and AMC-HN-8 cell lines were treated with the Akt inhibitor LY294002, mTOR inhibitor rapamycin, and dual inhibitor NVP-BEZ235 separately. The biological characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Despite substantial improvements in clinical management methods such as radiotherapy, chemotherapy, and surgery, the 5-year overall survival in LSCC has not improved significantly over the past 20 years [ 3 ]. In recent years, new targeted drugs have the hope of improving the prognosis of LSCC patients in the metastatic environment [ 4 ]. Therefore, the unraveling of the pathogenesis of LSCC is urgently needed to identify its diagnostic biomarkers and effective new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial improvements in clinical management methods such as radiotherapy, chemotherapy, and surgery, the 5-year overall survival in LSCC has not improved significantly over the past 20 years [ 3 ]. In recent years, new targeted drugs have the hope of improving the prognosis of LSCC patients in the metastatic environment [ 4 ]. Therefore, the unraveling of the pathogenesis of LSCC is urgently needed to identify its diagnostic biomarkers and effective new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Huang HY et al found that autophagy inhibitors significantly increased LC cell apoptosis and death both in vitro and in vivo . 28 The report of Chen L et al showed that miR-101 lowered the autophagy, proliferation and enhanced the apoptosis in LC cells. 29 In addition, studies have indicated that compared with normal laryngeal tissues, HPV-infected respiratory papilloma tissues have more LC3B expression and autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin binds handiest to at least one mTOR complicated, mTORC1, and inhibits handiest mTORC1-related signaling features 33 . This brought about the invention of ATP-aggressive mTOR inhibitors 34 that bind to each mTORC1 and mTORC2 and inhibit the kinase-based features of mTOR 35 .…”
mentioning
confidence: 99%